Relationship Between Glomerular Filtration Rate and Anemia in Chronic Kidney Disease Patients at RSUD Dr. H. Chasan Boesoirie - Pongsinaran, Fermat Mangiwa; Ambar, Edwin; The, Fera (Fakultas Kedokteran Universitas Malikussaleh, 2024)
Chronic kidney disease (CKD) is a condition of decreased kidney function with signs of damage to the kidneys or both, with a minimum duration of 3 months. CKD patients will experience anemia due to a decrease in the ability of the kidneys to produce erythropoietin in balance. The purpose of this study was to determine the relationship between glomerular filtration rate and anemia in CKD patients at Dr. H. Chasan Boesoirie Hospital. This type of research is analytic observational cross-sectional research using Spearman's rho test. The sample in this study were patients who were taken using the total sampling technique. Data collection tools in the form of medical records at Dr.H. Chasan Boesoirie Hospital in 2020-2022. This study found that the distribution of CKD patients was mostly female 52 patients (53.6%), most in the age group 55-64 years 36 patients (37.1%), most hemoglobin levels were found to be below normal or anemia 91 patients (93.1%), and most GFR in GFR <15 ml/min/1.73m2, namely 89 patients (91.8%). The results of bivariate analysis showed that there was a relationship between glomerular filtration rate and anemia with a p-value = 0.039 (p <0.05) and a correlation coefficient of 0.210 indicating that the direction of the correlation was positive with a very weak correlation strength. There is a relationship between glomerular filtration rate and anemia in patients with chronic kidney disease at Dr. H. Chasan Boesoirie Hospital.